RESPON PESERTA DIDIK TERHADAP MODEL PROBLEM BASED LEARNING PADA MATERI HUKUM NEWTON - Febi Perselia; Haratua Tiur Maria S; Erwina Oktavianty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aimed to determine students’ responses to the Problem Based Learning (PBL) on Newton’s Law material at Junior High School 5 Pontianak. This research was a survey. The sampling was taken Proposive Sampling method with intact group technique, thus students of VIII-A who have been given learning with PBL became the sample in the study. The research instrument was a response questionnairein in a total 10 statements with 3 response aspects. The analysis of students’ responses generally stated agreement with Problem Based Learning (PBL) of 78,53%, the results of the students’ to the Problem Based Learning (PBL) showed very interested criteria. Based on the finding, the Problem Based Learning model can be used as learning alternative to implementation learning. Keywords: Newton’s Law, Problem Based Learning, Responses